Effect of 9-cis Retinoic Acid Supplementation in Maturation Media on In Vitro Maturation of Murrah Buffalo Oocytes Derived by Ovum Pick-Up - Verma, Ekta; Singh, Prahlad; Singh, Narinder; Singh, Khushpreet; Mavi, Gurjot Kaur; Malik, Vijay Singh; Mahajan, Shashi Kant (The Indian Journal of Animal Reproduction, 2026)
Buffaloes are an important livestock species but their reproductive efficiency is constrained by fewer antral follicles, higher follicular atresia, and relatively poor oocyte quality compared to cattle. In vitro embryo production (IVEP) offers a potential solution, yet its success depends largely on optimizing in vitro maturation (IVM) conditions. Retinoic acid, an active metabolite of vitamin A, has been reported to enhance oocyte competence through improved cytoplasmic maturation, antioxidant defence, and mitochondrial activity. The present study evaluated the effect of 9-cis retinoic acid supplementation during IVM on cumulus expansion of oocytes derived by ovum pick-up (OPU) in Murrah buffaloes. A total of 279 follicles were aspirated from five buffaloes, yielding 209 cumulus–oocyte complexes (COCs) with a recovery rate of 74.9%. Of these, 74.2% were graded as culturable (Grades A, B, C). Following 22–24 hours of culture, the treat ment group showed a significantly higher proportion of oocytes with complete cumulus expansion (84.6% vs. 61.0%), while partial expansion (6.4% vs. 22.1%) and no expansion (8.9% vs. 15.6%) were significantly lower compared with the control (p< 0.05). These findings demonstrate that 9-cis retinoic acid at 5 nM concentration enhances cumulus expansion and improves oocyte competence, supporting its application as a valuable supplement for optimizing IVM protocols in buffaloes.